(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This study aimed to identify Principals’ Empowering Leadership and its relationship to job involvement from the perspective of female teachers in private schools. The descriptive analytical method was used, and the sample consisted of 148 of female teachers working at the Department of Education in Jeddah using simple random sampling. The study implied the questionnaire as a main tool for the study. The study concluded several results, the most important of which are; that the degree of Principals’ Empowering Leadership was very high in addition, the level of job involvement was very high too. The result showed also that there are statistically significant differences among study sample responses about the relationship between Empowering Leadership and job involvement due to age variable, and the differences were in favor of female teachers whose age is less than 25 years, and there are differences due to the variable of Years of experience, and the differences were in favor of female teachers whose years of experience are less than 10 years, and there were no statistically significant differences in the responses of the study sample about the relationship between Empowering Leadership and job involvement due to the educational qualification variable. Based on results, the researcher recommends several interventions, the most important of which are; Raising the level of female teachers’ awareness of the impact of their job on the overall effectiveness of the school, allowing female teachers to make important decisions quickly to meet the needs of beneficiaries, and believing in female teachers’ abilities to develop themselves even if they made some mistakes. Finally, the researchers recommend further studies on the potential leadership relationship with other variables in the school environment, with increasing attention to empowering workers as a modern management method that achieves many advantages in organizations.